Les ailes du crime ou la modernité de Détective - Mélodie Simard-Houde (Criminocorpus)
This article aims to study the various manifestations of aeronautics imaginaries, as their appear in Détective between 1928 and 1939. The representations of aviators and of aeronautical techniques take place in various genres and columns (such as criminal portraits, international newsreels, court reports, fictionnalized reportages, articles of technical vulgarization). In order to blend with the rubrics and poetics features of the weekly, these representations undergo some mutations that reveal how Détective operates a diversion of a mediatic intertext (literary, cinematographic and journalistic) that traces, in the same years, a heroic and epic tale of the conquest of the air. This is a paradoxal process, by which an object (aeronautics imaginaries) that has, at first view, very few things to do with criminality and “fait divers” is integrated to a periodic dedicated to this type of topics. Therefore, it highlights the modernity and the generic unicity (or “genericity”) of this media.